2021
DOI: 10.1088/1361-6382/ac1ccb
|View full text |Cite
|
Sign up to set email alerts
|

Discovering features in gravitational-wave data through detector characterization, citizen science and machine learning

Abstract: The observation of gravitational waves is hindered by the presence of transient noise (glitches). We study data from the third observing run of the Advanced LIGO detectors, and identify new glitch classes: fast scattering/crown and low-frequency blips. Using training sets assembled by monitoring of the state of the detector, and by citizen-science volunteers, we update the Gravity Spy machine-learning algorithm for glitch classification. We find that fast scattering/crown, linked to ground motion at the detect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 72 publications
0
87
0
Order By: Relevance
“…These classes are classified into different classes on unsupervised learning, whereas their characteristics are similar to Figure 3. A previous study 12 on supervised learning with the Gravity Spy labels indicated the existence of a subclass that might be in the "Scattered_Light" class. The unsupervised classification yielded the same results as in the previous study, indicating the existence of a subclass of the "Scattered_Light" class.…”
Section: Evaluation Of Our Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…These classes are classified into different classes on unsupervised learning, whereas their characteristics are similar to Figure 3. A previous study 12 on supervised learning with the Gravity Spy labels indicated the existence of a subclass that might be in the "Scattered_Light" class. The unsupervised classification yielded the same results as in the previous study, indicating the existence of a subclass of the "Scattered_Light" class.…”
Section: Evaluation Of Our Architecturementioning
confidence: 99%
“…Classifying transient noise could provide us with one of the clues to explore its origins and to improve the performance of the detector. Among others, the Gravity Spy project 10,11,12,13 is one of such efforts to classify transient noise. The Gravity Spy project used the Omicron software 14 to identify the signal of transient noise observed in the time-series data.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This would be especially beneficial for searches that require low latency, such as the early warning of binary neutron star mergers (Baltus et al, 2021 ; Yu et al, 2021 ). Other successful usage of ML techniques in GW astronomy include the identification of various GW events (Bayley et al, 2020 ; Chan et al, 2020 ; Dreissigacker and Prix, 2020 ; Huerta et al, 2020 ; Krastev, 2020 ; Schäfer et al, 2020 ; Wong et al, 2020 ; Beheshtipour and Papa, 2021 ; Chang et al, 2021 ; Chatterjee et al, 2021 ; López et al, 2021 ; Marianer et al, 2021 ; Mishra et al, 2021 ; Saiz-Pérez et al, 2021 ; Wei and Huerta, 2021 ; Yan et al, 2021 ), source parameter estimations (Gabbard et al, 2019 ; Chatterjee et al, 2020 ; Chua and Vallisneri, 2020 ; Green et al, 2020 ; Talbot and Thrane, 2020 ; Álvares et al, 2021 ; D'Emilio et al, 2021 ; Krastev et al, 2021 ; Williams et al, 2021 ; Xia et al, 2021 ), and detector characterization (Biswas et al, 2020 ; Colgan et al, 2020 ; Cuoco et al, 2020 ; Essick et al, 2020 ; Torres-Forné et al, 2020 ; Mogushi, 2021 ; Sankarapandian and Kulis, 2021 ; Soni et al, 2021 ; Zhan et al, 2021 ). Besides GW astronomy, the usage of CNNs has led to breakthroughs in a variety of topics related to time-series forecasting and classification (e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“…However, such sensitivity can be overwhelmed by intrinsic noises or local environment noises coupling into the instrument [6,7,8]. One common noise affecting the sensitivity of gravitational-wave detectors is scattered-light noise [9]. It originates when a fraction of laser light is undesirably scattered, reflected from moving surfaces, and recombined in any of the detectors' optical cavities [10].…”
Section: Introductionmentioning
confidence: 99%